PENGARUH KEPEMIMPINAN, PENGALAMAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA (KOMINFO) KABUPATEN LABUHANBATU - Hayati, Lusi Hijrah (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of leadership, work experience, work motivation and work discipline on employee performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. This type of research is associative research. Data collection in this study was carried out through a survey approach with quantitative descriptive research type by distributing questionnaires to 48 respondents, while the population used in this study were employees at the Office of Communication and Informatics (KOMINFO) Labuhanbatu Regency. The data collection technique is done by observation, interview, questionnaire and documentation study. The data analysis tool used in this study used SPSS (Statistical Package for The Social Sciences) version 16.0. The data analysis technique in this study is descriptive analysis and multiple linear regression analysis with hypothesis testing using partial significance test (t-test), simultaneous significant testing (f-test), and testing the coefficient of determination (R2). The results of this study indicate partially (t-test) it is known that leadership has a significant effect on employee performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. Work experience has a significant effect on employee performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. Work motivation has a significant effect on employee performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. Then work discipline has a significant effect on the performance of employees at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. In the simultaneous test (f-test) it is known that leadership, work experience, work motivation and work discipline have a significant effect on employee performance at the Office of Communication and Information Technology (KOMINFO) Labuhanbatu Regency. Through testing the coefficient of determination (R Square) 67.1% which can be explained by leadership, work experience, work motivation, and work discipline on employee performance. The remaining 32.9% is influenced by other variables which were not examined in this research.